Similarities and differences between lowland and mountain regions in the Republic of Srpska - Mirjanić, Stevo; Vaško, Željko; Ostojić, Aleksandar; Rokvić, Gordana; Mrdalj, Vesna; Drinić, Ljiljana; Figurek, Aleksandra (Economics of Agriculture, 2010)
Having taken the pre-war zoning in BiH as a starting point, in the Strategic Rural Development Plan of the Republic of Srpska its municipalities have been reclassified into the same regions. Based on the survey conducted in 802 rural households from 9 mountain and 3 lowland municipalities, analysis and comparison of the collected data between mountain and lowland regions have been done. The research has confrmed unequal development between rural households in mountain and lowland regions in reference to most of the considered characteristics. In comparison to lowland households, the ones in mountain regions dispose with more meadows and pastures, but fewer ploughed felds, have less capital equipment, generate lower income with non-agricultural activities making a major part. Moreover they are oriented towards livestock breeding, mountain villages have fewer communal infrastructure facilities and less access to health, education and other services. Due to all of these, additional effort should be invested in the future to reduce those differences by introducing special and differentiating already existing measures in order to direct them at faster and intensifed development of mountain region.